EKSPLORASI PROBIOTIK LOKAL UNTUK PERBAIKAN PEMBIBITAN DAN PEMBESARAN LELE SANGKURIANG - Indra Warman; Novita Hamron (UNIVED Press, Universitas Dehasen Bengkulu, 2020)
ABSTRACT Catfish is one type of freshwater fish that is quite popular with the people of Indonesia. Catfish prices are relatively cheap, easily cultivated, and have high nutritional content. Efforts to improve the yield of catfish farming have been done in many different ways, one of which is probiotics. The purpose of giving probiotics is to improve water quality. The study was conducted from April to July 2019, in the Experimental Pool of the Faculty of Agriculture, University of Ratu Samban, Bengkulu Utara, Bengkulu Province. The study used a two-factor randomized block design. The first factor is the type of probiotics (J), consisting of 2 levels, namely: J1: types of sea fish, J2: types of fresh fish. The second factor is the dose of probiotics (P), consisting of 4 levels, namely: P1: dose of 1 ml of probiotics per 10 liters of water, P2: dose of 1.5 ml of probiotics per 10 liters of water, P3: dose of 2 ml of probiotics per 10 liters water, P4: dose of 2.5 ml of probiotics per 10 liters of water. The above treatment was repeated three times so that there were 24 experimental units. This study aims to obtain information about the exploration of local probiotics with the right dosage for nursery improvement and enlargement of sangkuriang catfish. The results showed that the utilization of probiotic types / sources originating from both fresh fish and sea fish turned out to have the same effect, but there was potential that the types / sources of probiotic fish produced higher absolute weight and absolute length. Probiotic doses have the same potential between low and high doses, but there is a tendency that 1.5 ml / 10 l water probiotic doses produce higher absolute length and absolute weight. There is no interaction between the types of probiotics and probiotic doses. Keywords: waste, fish, probiotics, catfish, sangkuriang